ENGARUH LUAS LAHAN DAN MODAL TERHADAP PENDAPATAN PETANI SERAI WANGI DI DESA UJUNG KECAMATAN KUTA PANJANG KABUPATEN GAYO LUES - Khairil Anwar; Sartika Sartika (Jurnal Ekonomi Pertanian Unimal, 2020)
Thiis studdy aims to determine the effect of land area and capital partially on the income of farmers in the Desa Kuta Ujung, Kutapanjang Sub-district, Gayo Lues Regency. Thiis studdy usess primary data obtained by diistributing questiionnaires to 110 respondentts. The datta anallysis method used is multiiple liinear regressiion methods wiith the hellp off SPSS. The results partially show that land area and capital have a positive and significant effect on the income of lemongrass oil farmers in Desa Kuta Ujung, Kuta Panjang Sub-district, Gayo Lues Regency. Simultaneously, land area and capital have a positive and significant effect on the income of lemongrass oil farmers in Desa Kuta Ujung, Kuta Panjang Sub-district, Gayo Lues Regency. The magnitude of the iinfluence of tthe lland area and capital can explain the income of 92% in lemongrass oil farmers in Desa Kuta Ujung, Kuta Panjang Sub-district, Gayo Lues Regency.